2019
DOI: 10.1002/tkm2.1220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus paracasei A221‐fermented ginseng on impaired spatial memory in a rat model with cerebral ischemia and β‐amyloid injection

Abstract: Aim: Ginseng, a traditional herbal medicine, has been shown to prevent the progression of dementia, but its therapeutic effects vary because ginseng's components must first be activated by intestinal bacteria before being absorbed into the blood. We therefore focused on a fermented ginseng (FG), which contains activated components prepared by Lactobacillus paracasei A221, and compared its effects with those of non-FG. In this study, we investigated whether FG is effective on spatial memory impairment in rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Synaptic plasticity in the hippocampus was also evaluated. 59 Neuronal loss and apoptosis were assessed in some studies, 59,95 while microglial activation was measured in others. 96,97 Various biochemical parameters were evaluated across 26 studies, including brain cholinergic activity, Aβ peptide relevant biomarkers, brain-derived neurotrophic factor (BDNF), antioxidant activity, anti-inflammatory activity, and insulin signalling pathway.…”
Section: Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Synaptic plasticity in the hippocampus was also evaluated. 59 Neuronal loss and apoptosis were assessed in some studies, 59,95 while microglial activation was measured in others. 96,97 Various biochemical parameters were evaluated across 26 studies, including brain cholinergic activity, Aβ peptide relevant biomarkers, brain-derived neurotrophic factor (BDNF), antioxidant activity, anti-inflammatory activity, and insulin signalling pathway.…”
Section: Outcomementioning
confidence: 99%
“…Aβ-peptide-induced animal models were among the nontransgenic AD models used in the included studies. A total of four studies preferred Aβ 25-35 , 62,78,98,108 two preferred Aβ 1-42 59,95 and two preferred Aβ 40 . 111,112 Each Aβ peptide has its advantages and disadvantages when used to establish an AD animal model, and the choice of peptide will depend on the specific research question, as well as the availability and suitability of the peptide for the experimental design.…”
Section: Food and Function Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies [14,18,19,21,[23][24][25][26][27][28] showed that probiotic use could decrease neurological deficits and some claimed that it can improve spatial learning ability and cognitive function. Tests used to measure cognitive functioning in the studies include neurological function score [14,[18][19][20][21][22][23][24][25][26][27][28][29], Morris water maze [20,22,23], and open field test [20]. Morris water mazes were used to evaluate the capability of rodent spatial learning by navigating and locating the escape platform of the maze [30].…”
Section: Neurological Testmentioning
confidence: 99%
“…Most of the studies [9,[12][13][14][15][16][17][18][19][20] showed that probiotic use could de-crease neurological deficits and some claimed that it can improve spatial learning ability and cognitive function. Tests used to measure cognitive functioning in the studies include Neurological Function Score [9,[12][13][14][15][16][17][18][19][20][21][22][23], Morris Water Maze [15,22,23], and Open Field Test [23]. Morris water mazes were used to evaluate the capability of rodent spatial learning by navigating and locating the escape platform of the maze [24].…”
Section: Neurological Testmentioning
confidence: 99%